Effect of Communication, Work Ethics, Work Engagement and Work Environment on Employee Performance - Mulyani, Sitti Rizki; Ridwan, Muhammad; Yeni, Fitri (UPI YPTK Journal of Business and Economics, 2024)
This study aims to determine the effect of communication, work ethics, work involvement and work environment on employee performance at Bank Syariah Indonesia Padang Area Office. The population in this study were employees of Bank Syariah Indonesia (BSI) in the Padang area office, totalling 62 employees. The sampling technique is the total sample because the population is less than 100 respondents. The total sample in this study is the entire population, namely 62 employees—collecting data through surveys and distributing questionnaires to employees as respondents. The analytical method used is the outer and inner models test and the SmartPLS 3.0 data processing tools. The results show that communication, work ethics, work involvement, and work environment positively and significantly affect employee performance.